Getting respect or getting along with stigma?. Issue 8 (21st June 2017) - Simon, Patrick
ABSTRACT: By paying attention to the apparently minor forms of stigmatization, Getting Respect uncovers an underworld of threats that contribute to shape the sense of being disqualified and enlarge our understanding of racism and discrimination. In this paper, I engage with the main findings and argument of the book, especially the comparative dimension, questioning the status of the Israeli component of it. How "assaults on worth" that are key in this book are related to discrimination remain to be disentangled. One open question after reading this great research is whether we are facing a reformation of racism, with the new public debate on microaggression being both a symptom and a parameter of this evolution, or the book is a contribution to a deeper understanding of the expression of stigmatization in the same context of "racism without race" or "Laissez faire racism".